Multimessenger Search for the Sources of Cosmic Rays Using Cosmic Neutrinos - Halzen, Francis; Kheirandish, Ali (Frontiers in Astronomy and Space Sciences, 2019)
After updating the status of the measurements of the cosmic neutrino flux by the IceCube experiment, we summarize the evidence for the first identified source of cosmic rays and speculate on the connection between the two observations.